Consumo de álcool e pressão arterial: resultados da linha de base do ELSA-Brasil - Santana, Nathália Miguel Teixeira (2017)
The harmful effects of high consumption of alcohol are associated with the elevation of blood pressure. On the other hand, high blood pressure is the main risk factor for cardiovascular morbidity and mortality. The objective of this work is to evaluate the relationship between alcohol consumption and high blood pressure in participants of the baseline of the Brazilian Longitudinal Study of Adult Health (ELSA-Brasil). Out of the 15,105 baseline participants, those with use of anti-hypertension drugs, report of bariatric surgery, body mass index lower than 18.5 and higher or equal to 40Kg/m2 , and a percentile of alcohol consumption higher than 99 were excluded. The final sample was composed of 7,655 participants, between 35 and 74 years of age, and of both genders. Socioeconomic, hemodynamic, anthropometric, health and biochemical data was collected in a standardized way in six research and education institutions. Three blood pressure measures were done, with an interval of 1 minute resting, following protocol. The casual measure was considered as the average of those two blood pressure measurements. High blood pressure was defined by ≥140 mm systolic Hg and/or ≥90 mm Hg diastolic. Alcohol consumption was investigated by applying a specific questionnaire to evaluate the type of drink, the average weekly dosage, the quantity ingested at one occasion, and the consumption with meals. Alcohol consumption was estimated in grams per week and was categorized as abstainer, excessive and moderate, and by the pattern of ingestion as excessive, episodic and with meals. For analysis, statistical tests were done; and confusion factors were identified. The linear regression and logistics models were tested, with and without co-variable adjustments, and the significance level of 5% was adopted. The average consumption of beer, wine and distilled liquor was respectively of 1.906±2.239, 462±432, and 157±174mL/week. Arond 14% presented excessive alcohol consumption, and 25.3% excessive episodic consumption. Alcohol consumption was associated to high blood pressure in men that reported moderate (OR=1.69; IC95% 1.35-2.11) and excessive (OR=2.70; IC95% 2.04-3.59) consumption. In women, this association was significant only in the excessive consumption group (OR=2.86; IC95% 1.77-4.63). A higher chance for a raise in blood pressure was found among episodic excessive drinkers with a ≥2-3x/month (OR=1.69, IC95% 1.23-2.32), 1-2x/week (OR=1.49, IC95% 1.14-.94) and nearly daily/>1x/day (OR=2.15, IC95% 1.27-3.64), and who maintained after adjustment to alcohol consumption with meals. It is therefore concluded that the consumption of alcohol beverages raises the chance of high blood pressure, especially among excessive drinkers.